Evidence‐based complementary feeding recipe book for Kenyan caregivers: A novel approach - Lowe, A.; Callis, A.; DiGirolamo, A.; Girard, Amy W.; Boakye, A.; Ogutu, E.; Omosa, Esther B.; Okeyo, F.; Odollo, L.; Samburu, B.; Arimi, C.; Kamudoni, P.; et al. (Wiley, 2024)
The Kenyan Ministry of Health (MOH) and a consortium of nutritionists, researchers and communication, and design specialists developed a novel approach to create an evidence-based recipe book promoting complementary feeding (CF) in Kenya. The ADAPT approach includes five steps: applied research (A), dialogue with stakeholders (D), adapted behaviour change communication (BCC) theories (A), purpose-driven visual communication (P), and tailoring to priority audiences (T). Through this approach, the recipe book addresses key knowledge gaps using behaviour change theories and visual communication best practice to increase accessibility, acceptability, retention and motivation for behaviour change. The book addresses barriers to CF identified through formative applied research. Dialogue with stakeholders helped ensure cultural appropriateness and the book's alignment with MOH recommendations and key messages. The book uses behaviour change theories to approach the reader in a respectful way that motivates behaviour change. The use of consistent, purpose-driven visuals helps ensure key messages are easily understood and accessible to all caregivers regardless of literacy level. The book's tone and content are tailored to its audiences’ attributes, needs and preferences. This five-step process inspired the development of ADAPT, a novel approach that integrates behaviour change and visual communication for greater impact. This paper outlines how the consortium used the ADAPT approach to develop an evidence-based book that thoughtfully and holistically addresses a wide range of barriers, provides practical solutions and increases self-efficacy around CF. It offers a blueprint for public health practitioners from any field who are interested in using visual behaviour change communication to promote healthy behaviour.